Surface coated cutting tools
Patent Information
- Application Number
- JP2021049159
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-23
- Publication Date
- 2025-01-09
- Estimated Expiration
- 2041-03-23
AI Technical Summary
【0015】 前記によれば、耐欠損性の向上した表面被覆切削工具を得ることができる。
Smart Images

Figure 0007610781000010 
Figure 0007610781000011 
Figure 0007610781000012
Abstract
Description
[Technical field]
[0001] The present invention relates to a surface-coated cutting tool (hereinafter sometimes referred to as a coated tool). [Background technology]
[0002] 2. Description of the Related Art Conventionally, coated tools have been known in which a coating layer is formed on the surface of a tool substrate such as a tungsten carbide (hereinafter referred to as WC)-based cemented carbide, and are known to exhibit excellent wear resistance. In order to improve the durability of the coated tool, various proposals have been made for improving the coating layer.
[0003] For example, in Patent Document 1, a (Al 1-x V x The document describes a coated tool coated with any one of nitrides, carbonitrides, oxynitrides, and oxycarbonitrides of the above-mentioned metals (x is 0.24 to 0.45), and it is said that the coated tool prevents chipping or breakage of the cutting edge and peeling of the coating layer and has good wettability. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2005-271106 A Summary of the Invention [Problem to be solved by the invention]
[0005] The present invention has been made in consideration of the above circumstances and proposals, and has an object to provide a coated tool having improved fracture resistance. [Means for solving the problem]
[0006] The surface-coated cutting tool according to an embodiment of the present invention comprises: A tool substrate and a coating layer on a surface of the tool substrate, 1) The coating layer has an average thickness of 1.0 to 20.0 μm and a composition represented by the formula: (V 1-x Al x )(C y N 1-y ), the average content ratio of x is x avg is 0.76 to 0.95, and the average content ratio of y is y avg A composite nitride layer or composite carbonitride layer of V and Al having a V / Al ratio of 0.000 to 0.015, 2) The composite nitride layer or composite carbonitride layer has composite nitride or composite carbonitride crystal grains having a NaCl type face-centered cubic structure, 3) In a frequency distribution of inclination angles of the normal direction of each {111} plane of the crystal grain relative to the normal direction of the surface of the tool base, the inclination angles in the range of 0 to 45 degrees are divided into increments of 0.25 degrees, and the maximum frequency is found in one of the 0 to 10 degree divisions, and the sum of the frequency distribution of the 0 to 10 degree divisions accounts for 45% or more of the total sum of the frequencies of the inclination angle distribution.
[0007] Furthermore, the surface-coated cutting tool according to the above embodiment may satisfy one or more of the following items (1) to (7), provided that it does not simultaneously satisfy items (4) and (5).
[0008] (1) The crystal grains are Area-weighted average Average crystal grain width: 0.1 to 2.0 μm, Area-weighted average The columnar crystals have an average aspect ratio of 2.0 to 10.0. <001> and the difference Δx between the average value of the maximum value and the average value of the minimum value of x is 0.03 to 0.10.
[0009] (2) the crystal grains are columnar crystals having an average crystal grain width of 0.1 to 2.0 μm and an average aspect ratio of 2.0 to 10.0; <001> The grains have a repeating change in which the Al content ratio has a maximum value and a minimum value along any one of the equivalent crystal orientations represented by the following formula (1): the average interval of the repeating change is 3 to 100 nm, and the change width x0 of x in a plane perpendicular to the orientation is 0.01 or less.
[0010] (3) The lattice constant a of the crystal grains is the lattice constant a of cubic VN. VN and the lattice constant a of cubic AlN AlN For 0.05a VN +0.95a AlN ≦a≦0.24a VN +0.76a AlN To satisfy the relationship.
[0011] (4) The composite nitride or composite carbonitride layer is Complex nitrides or complex carbonitrides with NaCl-type face-centered cubic structure It consists of only crystal grains.
[0012] (5) In the composite nitride or composite carbonitride layer, fine crystal grains having a hexagonal crystal structure are present, the area ratio of the fine crystal grains is 30% or less, and the average grain size is 0.01 to 0.30 μm.
[0013] (6) Between the tool substrate and the V-Al composite nitride layer or composite carbonitride layer, there is a lower layer which is composed of one or more Ti compound layers selected from the group consisting of a Ti carbide layer, a nitride layer, a carbonitride layer, a carbonate layer and a carbonitride-oxycarbonate layer, and has a total average layer thickness of 0.1 to 20.0 μm.
[0014] (7) An upper layer containing at least an aluminum oxide layer is present on the upper portion of the composite nitride layer or composite carbonitride layer, and has a total average layer thickness of 1.0 to 25.0 μm. Effect of the Invention
[0015] According to the above, a surface-coated cutting tool having improved fracture resistance can be obtained. [Brief description of the drawings]
[0016] [Figure 1] 1 is a schematic diagram showing a vertical cross section of a coating layer of a surface-coated cutting tool according to an embodiment of the present invention. FIG. [Diagram 2] FIG. 2 is a diagram showing a schematic diagram of a change in the content ratio in a crystal grain of an NaCl type face-centered cubic structure having a repeated change in the content ratio of Al. [Diagram 3] FIG. 2 is a schematic diagram showing repeated changes in the Al content. [Figure 4] FIG. 2 is a schematic perspective view of a portion of a gas supply pipe of an example of an apparatus for manufacturing the surface-coated cutting tool according to the present embodiment. [Diagram 5] 5 is a schematic cross-sectional view of the gas supply pipe in FIG. 4. [Figure 6] 5 is a schematic cross-sectional view showing a gas outlet of the gas supply pipe in FIG. 4. [Figure 7] FIG. 13 is a graph showing the frequency distribution of the inclination angle between the normal direction of the surface of the tool base body in Example 3 and the normal direction of the {111} plane of a crystal grain having a NaCl-type face-centered cubic structure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] The present inventors have conducted research on coated tools coated with a composite nitride layer or composite carbonitride layer of V and Al (hereinafter, sometimes referred to as a (VAl)(CN) layer) and have found that simply coating with a composite nitride layer or composite carbonitride layer of V and Al does not provide sufficient chipping resistance.
[0018] As a result of further investigation, it was discovered that chipping resistance can be improved by orienting the normal direction of the {111} plane of the (VAl)(CN) layer in a specific manner perpendicular to the surface of the tool base (normal direction to the surface of the tool base).
[0019] Hereinafter, a surface-coated cutting tool according to an embodiment of the present invention will be described. In this specification and claims, when a numerical range is expressed as "L to M" (where L and M are both numerical values), the range includes an upper limit value (M) and a lower limit value (L), and the upper limit value (M) and the lower limit value (L) have the same units.
[0020] I. Covering layer The coating layer (2) of this embodiment is present on the surface of the tool substrate (1) and includes a (VAl)(CN) layer (3) as shown in Fig. 1. A lower layer (4) may be present between the tool substrate (1) and the (VAl)(CN) layer (3), and an upper layer (5) may be present on the surface of the (VAl)(CN) layer. The following description will focus on the (VAl)(CN) layer.
[0021] 1.(VAl)(CN) layer (1) Average layer thickness The average thickness of the (VAl)(CN) layer is preferably 1.0 to 20.0 μm. The reason is that if the average thickness is less than 1.0 μm, the average thickness is too thin to ensure sufficient wear resistance over long-term use, while if the average thickness exceeds 20.0 μm, the crystal grains of the (VAl)(CN) layer tend to become coarse, making chipping more likely to occur.
[0022] (2) Composition The composition of the (VAl)(CN) layer is expressed by the formula: (V 1-x Al x )(C y N 1-y ), the average content ratio of x is x avg is 0.76 to 0.95, and the average content ratio of y is y avg is preferably 0.000 to 0.015.
[0023] The reasons are as follows: avg If y is less than 0.76, the wear resistance of the (VAl)(CN) layer is insufficient, while if it exceeds 0.95, the (VAl)(CN) layer is easily embrittled and the chipping resistance is reduced. avgWhen the thickness is within the above range, the adhesion between the (VAl)(CN) layer and the tool base or the lower layer described below is improved, the impact during cutting is mitigated, and the chipping resistance of the coating layer is reliably improved.
[0024] In addition, (V 1-x Al x ) and (C y N 1-y ) is not particularly limited, but (V 1-x Al x ) is set to 1, (C y N 1-y The ratio of (V) is preferably 0.8 to 1.2. 1-x Al x ) for (C y N 1-y ) within the above range, the object of the present invention can be achieved more reliably.
[0025] (3) NaCl type face-centered cubic structure The (VAl)(CN) layer preferably contains crystal grains having a NaCl-type face-centered cubic structure. That is, in a longitudinal section (a section perpendicular to the surface of the tool base when the surface is treated as a flat surface ignoring minute irregularities on the surface of the tool base), the area ratio of crystal grains having a NaCl-type face-centered cubic structure is 60% or more, more preferably 80% or more, and all crystal grains (area ratio 100%) may have a NaCl-type face-centered cubic structure.
[0026] (4) Tilt distribution in the normal direction of the {111} plane For the (VAl)(CN) layer, electron backscatter diffraction (EBSD) was used to determine the crystal grains with a NaCl-type face-centered cubic structure. [1] Measure the inclination angle of the normal direction of the {111} plane of this crystal grain (the direction indicated by (7) in Figure 2) relative to the normal direction of the tool base surface. [2] Divide the inclination angle within the range of 0 to 45 degrees into increments of 0.25 degrees. [3] When the frequency distribution of the inclination angle is calculated by tallying up the frequencies in each category, In the obtained inclination angle frequency distribution, it is preferable that the highest peak (maximum frequency) is in one of the sections in the range of 0 to 10 degrees, and the sum of the frequencies in this range of 0 to 10 degrees is 45% or more of the sum of the frequencies in the range of 0 to 45 degrees. This proportion is more preferably 50% or more, and even more preferably 55% or more. By having such a distribution of the inclination angles, grain boundary sliding of crystal grains is suppressed and toughness is improved, so that the chipping resistance of the coating layer is reliably improved.
[0027] In determining the inclination angle number distribution, in the case of an ideal random orientation, the inclination angle number is normalized so that it is a constant value regardless of the inclination angle between the normal direction of a crystal plane and the normal direction of the surface of the tool base.
[0028] Here, the surface of the tool substrate is defined as the average line of the interface roughness between the tool substrate and the coating layer in the observation image of the longitudinal section. That is, when the tool substrate has a flat surface like an insert, element mapping is performed on the longitudinal section using energy dispersive X-ray spectroscopy (EDS), and the obtained element map is subjected to known image processing to determine the interface between the coating layer (if a lower layer, which will be described later, exists, the lower layer is used instead of the coating layer) and the tool substrate, and the average line is arithmetically obtained for the roughness curve of the interface between the coating layer and the tool substrate thus obtained, and this is defined as the surface of the tool substrate. The direction perpendicular to this average line is defined as the direction perpendicular to the tool substrate (layer thickness direction).
[0029] Even if the tool base has a curved surface like a drill, if the tool diameter is sufficiently large compared to the thickness of the coating layer, the interface between the coating layer and the tool base in the measurement area will be approximately flat, so the surface of the tool base can be determined by a similar method. That is, for example, in the case of a drill, element mapping is performed using EDS on the longitudinal section of the coating layer in a section perpendicular to the axial direction, and the interface between the coating layer and the tool base is determined by performing known image processing on the obtained element map, and the average line is arithmetically obtained for the roughness curve of the interface between the coating layer and the tool base thus obtained, and this is taken as the surface of the tool base. Then, the direction perpendicular to this average line is taken as the direction perpendicular to the tool base (layer thickness direction).
[0030] (5) Average particle width and aspect ratio The crystal grains having a NaCl type face-centered cubic structure in the (VAl)(CN) layer are more preferably columnar crystals having an average crystal grain width of 0.1 to 2.0 μm and an average aspect ratio of 2.0 to 10.0.
[0031] The reason is that when the average grain width is smaller than 0.1 μm, the increase in grain boundaries reduces the plastic deformation resistance and the oxidation resistance, which can lead to abnormal damage. On the other hand, when the average grain width W is larger than 3.00 μm, the toughness is likely to decrease due to the presence of coarsely grown grains.
[0032] Furthermore, when the average aspect ratio of granular crystals is smaller than 2.0, the interface (grain boundary) is likely to become the starting point of fracture due to the shear stress generated on the surface of the coating layer during cutting, resulting in chipping. On the other hand, when the average aspect ratio exceeds 10.0, micro-chipping occurs at the cutting edge during cutting, and when chipping occurs in the adjacent columnar structure, the resistance to the shear stress generated on the surface of the coating layer is likely to be small, and the damage will progress rapidly as the columnar structure breaks, resulting in large chipping.
[0033] Here, the method of calculating the average grain width and the average aspect ratio will be described. First, the grain boundaries are determined in a 50 μm observation field (longitudinal section) of the coating layer in a direction parallel to the tool substrate. The method for determining the grain boundaries is to use an electron backscatter diffraction device to analyze the observation field plane two-dimensionally at intervals of 0.01 μm to determine measurement points having a crystal lattice of NaCl type face-centered cubic structure in the observation field plane. If there is an orientation difference of 5 degrees or more between adjacent measurement points (hereinafter referred to as pixels) among the measurement points having a crystal lattice of NaCl type face-centered cubic structure, or if adjacent pixels do not have a crystal lattice of NaCl type face-centered cubic structure, the boundary between the pixels is defined as a grain boundary.
[0034] The area surrounded by the grain boundary is defined as one crystal grain. However, a single pixel that has an orientation difference of 5 degrees or more with all of its neighboring pixels is not considered a crystal grain, but a pixel that is connected to two or more pixels is treated as a crystal grain. In this way, the grain boundary is determined and the crystal grain is identified.
[0035] Next, the maximum length H of a certain crystal grain i in the direction perpendicular to the surface of the tool base (layer thickness direction) i , the grain width W, which is the maximum length parallel to the surface of the tool base i , and area S i The aspect ratio A of grain i is calculated. i A i =H i / W i In this way, the grain widths W1 to W2 of at least 20 or more (i = 1 to 20 or more) crystal grains in the observation field are calculated. n (n≧20) is area-weighted averaged by [Equation 1] to obtain the average grain width W of the crystal grains. Similarly, the aspect ratios A1 to A n (n≧20) is determined, and the area-weighted average is calculated using [Equation 2] to determine the average aspect ratio A of the crystal grains.
[0036]
number
[0037]
number
[0038] (6) Repeated changes in Al content [1] Maximum and minimum values As shown in FIG. 2, the crystal grain (6) having a NaCl type face-centered cubic structure in the (VAl)(CN) layer is <001> It is more preferable that the Al content (i.e., the V content) has a repeated change along one orientation (10) of the equivalent crystal orientations represented by the following formula:
[0039] Here, the Al content (i.e., the V content) refers to, for example, the change shown diagrammatically in Fig. 3. In Fig. 3, the maximum value and the minimum value are the same value, and the interval between adjacent maximum values and minimum values is also the same, but the repeated change in the Al content in this specification and claims means that the Al content changes so that the Al content alternates between maximum values and minimum values, and the maximum values and minimum values may or may not be the same value, and the interval between adjacent maximum values and minimum values may or may not be the same.
[0040] The difference between the average maximum and minimum values of the Al content is calculated based on the above formula: (V 1-x Al x )(C y N 1-y It is more preferable that the difference (Δx) in x in the above formula (1) is 0.03 to 0.10. This produces appropriate distortion in the crystal grains having a NaCl-type face-centered cubic structure, and reliably improves the hardness of the coating layer.
[0041] That is, if Δx is less than 0.03, the above-mentioned strain is small and the coating layer may not have sufficient hardness, whereas if Δx exceeds 0.10, the strain becomes too large, increasing lattice defects and decreasing the hardness of the coating layer.
[0042] [2] Interval of repeated changes The average value of the repetition interval between the maximum and minimum values is more preferably 3 to 100 nm, because if it is less than 3 nm, the toughness of the coating layer may decrease, whereas if it exceeds 100 nm, improvement in the hardness of the coating layer may not be expected.
[0043] The interval between the maximum and minimum values is the grain size. <001> The Al content is measured and graphed by performing a line analysis along one of the equivalent crystal orientations represented by the following formula: In addition, when graphing and analyzing, a known noise removal method (for example, the moving average method) is used.
[0044] That is, as shown in Fig. 3, a straight line m is drawn across the curve showing the repeated change in the Al content ratio. This straight line m is drawn so that the area of the region surrounded by the curve is equal on the upper and lower sides of the line m. Then, for each region where the line m crosses the curve showing the repeated change in the Al content ratio, the maximum or minimum value of the Al content ratio is found and the distance between the two is measured, and the measured values at multiple points are averaged to find the average distance of the repeated change in the Al content ratio in (VAl)(CN).
[0045] [3] A plane perpendicular to the direction of repeated changes Furthermore, in a plane perpendicular to the direction in which the Al content ratio repeatedly changes between the maximum and minimum values (a plane having a normal line in the direction in which the repeated changes occur; in FIG. 2, a plane having a normal line in the direction of number (10)), the composition formula: (V 1-x Al x )(C y N 1-y It is more preferable that the variation range of x in (i.e., the difference between the maximum value and the minimum value) x0 is 0.01 or less. When x0 is within this range, the hardness and chipping resistance of the coating layer are improved more reliably.
[0046] (7) Lattice constants of crystal grains with NaCl-type face-centered cubic structure For the (VAl)(CN) layer, an X-ray diffraction test was performed using an X-ray diffractometer with Cu-Kα radiation as the radiation source to determine the lattice constant a of the crystal grains of the NaCl type face-centered cubic structure. The lattice constant a was found to be equal to the lattice constant a of cubic VN (JCPDS00-035-0768). VN : 4.1392Å and the lattice constant a of cubic AlN (JCPDS00-046-1200) AlN : 0.05a for 4.0450Å VN +0.95a AlN =4.050≦a≦0.24a VN +0.76a AlN =4.068. When this relationship is satisfied, the (VAl)(CN) layer exhibits higher hardness, and thus has better impact resistance in addition to better wear resistance.
[0047] (8) Microcrystalline grains with hexagonal crystal structure When the (VAl)(CN) layer is observed in cross section, each of the crystal grains having a NaCl-type face-centered cubic structure is a columnar crystal, and fine crystal grains having a hexagonal structure may be present at the grain boundaries with an area ratio of 30% or less.
[0048] When the fine crystal grains having a hexagonal structure are present at an area ratio of 30% or less, the slippage at the grain boundaries of the crystal grains having a NaCl type face-centered cubic structure is suppressed, and the toughness of the coating layer is reliably improved. However, when the area ratio exceeds 30%, the number of crystal grains having a NaCl type face-centered cubic structure decreases, and the hardness of the coating layer may decrease.
[0049] The average grain size of the microcrystal grains having a hexagonal crystal structure is more preferably 0.01 to 0.30 μm, because if the average grain size is less than 0.01 μm, the above-mentioned grain boundary sliding may not be sufficiently suppressed, whereas if it exceeds 0.30 μm, the strain within the coating layer may become large, causing the hardness of the coating layer to decrease.
[0050] Here, the average grain size is determined by finding the area of a fine crystal grain and figuring out the diameter of a circle corresponding to the area.
[0051] 2. Lower layer The coating layer including the (VAl)(CN) layer of this embodiment sufficiently achieves the above-mentioned object, but when a lower layer is provided which is made of one or more Ti compound layers selected from the group consisting of Ti carbide layers, nitride layers, carbonate layers, and carbonitride layers and has a total average thickness of 0.1 to 20.0 μm, the coated tool exhibits more excellent properties in combination with the effects of this layer. However, when a lower layer is provided which is made of one or more Ti compound layers selected from the group consisting of Ti carbide layers, nitride layers, carbonate layers, and carbonitride layers, if the total average thickness of the lower layer is less than 0.1 μm, the function of the lower layer is not fully exhibited, whereas if it exceeds 20.0 μm, the crystal grains tend to become coarse, and chipping is likely to occur.
[0052] 3. Upper layer In addition, when an upper layer having a total average layer thickness of 1.0 to 25.0 μm including an aluminum oxide layer is provided on the coating layer including the (VAl)(CN) layer of this embodiment, the excellent properties of the coated tool are further exhibited, which is preferable. If the total average layer thickness is less than 1.0 μm, the upper layer does not fully function, while if it exceeds 25.0 μm, chipping is likely to occur.
[0053] II. Tool base (1)Material The material may be any of the conventionally known materials for tool substrates, provided that it does not impede the achievement of the object of the present invention. For example, it is preferable to use any of the following: cemented carbide (WC-based cemented carbide, WC, Co, and carbonitrides such as Ti, Ta, Nb, etc.), cermet (mainly composed of TiC, TiN, TiCN, etc.), ceramics (titanium carbide, silicon carbide, silicon nitride, aluminum nitride, aluminum oxide, etc.), and cBN sintered body.
[0054] (2) Shape There are no particular limitations on the shape of the tool body as long as it is a shape that can be used as a cutting tool, and examples of the shape include the shape of an insert and the shape of a drill.
[0055] III. Manufacturing method The (VAl)(CN) layer of this embodiment can be manufactured by a CVD method using, for example, a gas group A consisting of NH3 gas and H2 gas, and a gas group B consisting of VCl4, AlCl3, N2, and H2.
[0056] Here, gas group A and gas group B are supplied separately to the space in the reaction vessel of the thermal CVD apparatus up to just before the object to be deposited, and then gas group A and gas group B are mixed and reacted just before the object to be deposited. This is effective for uniformly supplying gas species with high reactivity to each other over the deposition region to uniformly deposit a coating. The detailed technical content is disclosed, for example, in Japanese Patent No. 6511798.
[0057] The film formation apparatus described in this publication has a gas supply pipe shown in FIGS. 4 to 6, and its structure will be described below. As shown in Figures 4 and 5, the gas supply pipe (11), which is a cylindrical pipe that rotates at a predetermined rotational speed around its center (13), has its interior divided into approximately two equal parts by a partition member (12) extending along its axial direction, and has a gas group A flow section (14) and a gas group B flow section (15).
[0058] As shown in FIG. 4, the gas supply pipe (11) is provided with a plurality of gas group A outlets (16) and gas group B outlets (17) arranged along the height direction and constituting a pair of outlets (20) located at approximately the same height.
[0059] The gas group A nozzle (16) and the gas group B nozzle (17) shown in FIG. 5 belong to the same nozzle pair (20), and the angle between the center (18) of the outer circumferential opening end of the gas group A nozzle (16) and the center (19) of the outer circumferential opening end of the gas group B nozzle (17) is α.
[0060] 6, the relative angle around the axis between the raw material gas group A outlets 16 in two outlet pairs (20) adjacent to each other in the height direction (axial direction) is β1, and the relative angle around the axis between the raw material gas group B outlets 17 in two outlet pairs (20) adjacent to each other in the height direction (axial direction) is β2. The relative angles around the axis between the gas group A outlet (16) and the gas group B outlet (17) adjacent to each other in the height direction (axial direction) are γ1 and γ2, respectively.
[0061] IV.Measurement method (1) Average layer thickness After determining the surface of the tool base as described above, measurements are taken along multiple analysis lines (e.g., five lines) along a direction perpendicular to the surface of the tool base. The average thickness of the (VAl)(CN) layer is determined by determining the thickness of each analysis line and averaging it to determine the average thickness, which is defined as the boundary with the adjacent layer where Al atoms appear and their content rate reaches 1 atomic %.
[0062] (2) Composition The composition of the (VAl)(CN) layer is determined as follows. Average Al content x avg The average Al content x was calculated by irradiating the surface of a polished sample with an electron probe microanalyser (EPMA) from the surface of the sample and averaging the 10-point analysis results of the characteristic X-rays obtained. avg Request.
[0063] Average content of C y avg The concentration of the components released by the sputtering effect was measured in the depth direction by irradiating an ion beam onto a 70 μm × 70 μm area from the surface of the sample.
[0064] (3) Crystal grains with NaCl-type face-centered cubic structure The crystal structure of the (VAl)(CN) layer is identified by electron diffraction using a transmission electron microscope (TEM), it is confirmed that it is a NaCl-type face-centered cubic structure, and its area ratio is calculated.
[0065] (4) Slope angle number distribution Regarding the distribution of the tilt angles of the (VAl)(CN) layer, the sample is set in the barrel of a field emission scanning electron microscope (FE-SEM) with the longitudinal section as the polished surface, and an electron beam with an accelerating voltage of 15 kV and a projection current of 1 nA is irradiated to each of the crystal grains having a NaCl-type face-centered cubic structure present within the measurement range of the polished cross-section surface at an incident angle of 70 degrees on the polished surface.
[0066] Using the EBSD method, the inclination angle of the normal to the {111} crystal plane of the (VAl)(CN) layer relative to the normal to the tool base surface (the direction perpendicular to the tool base surface at the polished surface) is measured at intervals of 0.01 μm / step for the coating layer within a measurement range of 50 μm in length horizontally to the tool base surface and up to the layer thickness along a cross section perpendicular to the tool base surface.
[0067] Then, based on the measurement results, the measured tilt angles within the range of 0 to 45 degrees are divided into sections at intervals of 0.25 degrees, and the degrees within each section are tallied to confirm the presence of a peak degree (highest degree) within the range of 0 to 10 degrees, and to determine the proportion of degrees within the range of 0 to 10 degrees. EXAMPLES
[0068] The present invention will be described below with reference to examples, but the present invention is not limited to these examples. That is, an insert cutting tool using a WC-based cemented carbide as the tool base will be described, but the material of the tool base may be any of those described above, and the shape of the tool base may be a drill or the like, as described above.
[0069] 1. Manufacturing of the tool base As raw material powders, WC powder, TiC powder, TaC powder, NbC powder, Cr3C2 powder and Co powder, all having an average particle size of 1 to 3 μm, were prepared. These raw material powders were mixed according to the composition shown in Table 1, wax was added, and the mixture was mixed in a ball mill in acetone for 24 hours. After drying under reduced pressure, the mixture was pressed into a green compact of a predetermined shape at a pressure of 98 MPa.
[0070] The green compact was then vacuum sintered at a predetermined temperature in the range of 1370 to 1470°C for 1 hour in a vacuum of 5 Pa. After sintering, tool bases A to C made of WC-based cemented carbide having the insert shape of Mitsubishi Materials Corporation's LOGU1207040PNER-M were produced.
[0071] 2. Film formation A (VAl)(CN) layer was formed on the surface of each of the tool substrates A to C using a CVD apparatus to obtain Examples 1 to 10 shown in Tables 5 and 6. The film formation conditions were as shown in Table 2, and were generally as follows:
[0072] Reaction gas composition (the content of gas components is expressed as volume percent, with the total of Gas Group A and Gas Group B being 100 volume percent): Gas group A NH3: 1.0-1.5%, H2: 55-60% Gas group B: AlCl3: 0.6-0.9%, VCl4: 0.2-0.3%, Al(CH3)3:0.0~0.5%, N2:0.0~12.0%, H2: remaining Reaction atmosphere pressure: 4.5~5.0kPa Reaction atmosphere temperature: 700~850℃
[0073] Here, gas group A and gas group B were supplied as source gas A and source gas B, respectively, to the CVD apparatus described in the above-mentioned Japanese Patent No. 6511798. The rotation speed of the gas supply pipe and the nozzle angle of the gas supply pipe were as follows: Gas supply pipe rotation speed: 5~20rpm Gas supply pipe nozzle angle: α: 180° β1 and β2: 155° γ1 and γ2: 25°
[0074] In addition, for Examples 4 to 10, the lower layer and / or upper layer shown in Table 4 were formed under the conditions shown in Table 3.
[0075] For comparison, a (VAl)(CN) layer was formed on the surface of tool substrates A to C under the film-forming conditions shown in Table 2, and Comparative Examples 1 to 10 shown in Tables 5 and 6 were obtained. In the comparative example process, the source gas was not separated into two systems but was supplied into the reaction chamber of the thermal CVD apparatus from one gas supply pipe. Therefore, a gas supply pipe was used that did not distinguish between the gas group A nozzle (16) and the gas group B nozzle (17) and did not have a nozzle pair (20). In addition, for Comparative Examples 4 to 10, the lower layer and / or the upper layer shown in Table 4 were formed under the conditions shown in Table 3.
[0076] For the above-mentioned Examples 1 to 10 and Comparative Examples 1 to 10, the average Al content x avg and the average C content y avg In addition, in the distribution of the number of inclination angles of the normal line of the {111} plane relative to the normal direction of the tool base surface, it was confirmed whether the maximum frequency of the number of inclination angles was in the range of 0 to 10 degrees, and the proportion of the frequency in which the inclination angle was in the range of 0 to 10 degrees was calculated. <001> The presence or absence of repeated changes in the Al content along the equivalent orientation represented by (a), the difference between the average maximum and minimum values of the Al content, the average repeat interval, and further the change in the Al content in the plane perpendicular to the orientation were also measured.
[0077] In addition, the proportion of crystal grains having a NaCl-type face-centered cubic structure, the lattice constants of TiN and AlN having a NaCl-type face-centered cubic structure, and the area proportion of fine crystal grains existing at the grain boundaries of columnar crystals having a NaCl-type face-centered cubic structure were measured. The average layer thickness was determined by observing the longitudinal section of each constituent layer using a scanning electron microscope (magnification: 5000 times), measuring the layer thickness at five points within the observation field, and averaging the results.
[0078] These results are summarized in Tables 5 and 6. Fig. 7 shows the frequency distribution of the inclination angle between the normal direction of the surface of the tool base body in Example 3 and the normal direction of the {111} plane of the crystal grains of the NaCl type face-centered cubic structure.
[0079] [Table 1]
[0080] [Table 2]
[0081] [Table 3]
[0082] [Table 4]
[0083] [Table 5]
[0084] [Table 6]
[0085] Next, for Examples 1 to 10 and Comparative Examples 1 to 10, a wet face milling test was carried out on alloy steel SCM440 with each sample clamped to the tip of a tool steel cutter with a cutter diameter of 32 mm using a fixing jig, and the flank wear width of the cutting edge was measured.
[0086] Cutting test: Wet face milling Work material: JIS / SCM440 width Cutting speed: 180m / min Cutting depth ap: 6.0mm Cut ae: 20mm Feed per blade: 0.15mm / blade Cutting time: 80 minutes
[0087] The results of the cutting test are shown in Table 7. For Comparative Examples 1 to 10, the cutting edge fracture caused the tool to reach the end of its life, so the time to reach the end of its life is shown.
[0088] [Table 7]
[0089] As is clear from the results shown in Table 7, none of the examples experienced chipping at the cutting edge, and chipping resistance was improved, demonstrating excellent cutting performance over a long period of time. In contrast, in all of Comparative Examples 1 to 10, chipping occurred at the cutting edge, and the cutting edge reached the end of its useful life in a short period of time. [Explanation of symbols]
[0090] 1 Tool base 2 Covering layer 3 (VAl)(CN) layer 4 Lower Layer 5 Upper layer 6. Grains with NaCl-type face-centered cubic structure in the (VAl)(CN) layer 7. Normal direction of {111} plane of crystal grains with NaCl type face-centered cubic structure in (VAl)(CN) layer 8 Regions with relatively high Al content 9 Region with relatively low Al content 10 <001> The equivalent crystal orientation is represented by 11 Gas supply pipe 12 Partition material 13 Center of gas supply pipe 14 Gas Group A Distribution Section 15 Gas Group B Distribution Section 16 Gas group A outlet 17 Gas group B outlet 18 Center of the outer peripheral opening end of the gas group A nozzle 19 Center of the outer peripheral opening end of the gas group B nozzle 20 Nozzles α Angle β1 Angle β2 Angle γ1 Angle γ2 Angle
Claims
1. A surface-coated cutting tool having a tool substrate and a coating layer on a surface of the tool substrate, 1) The coating layer has an average thickness of 1.0 to 20.0 μm and a composition represented by the formula: (V 1-x A x ) (C y N 1-y ) the average content ratio of x is x avg is 0.76 to 0.95, and the average content ratio of y is y avg A composite nitride layer or composite carbonitride layer of V and Al having a V / Al ratio of 0.000 to 0.015, 2) The composite nitride layer or composite carbonitride layer has composite nitride or composite carbonitride crystal grains having a NaCl type face-centered cubic structure, 3) In a frequency distribution of inclination angles of the normal direction of each {111} plane of the crystal grain relative to the normal direction of the surface of the tool base, the inclination angles in the range of 0 to 45 degrees are divided into increments of 0.25 degrees, and the maximum frequency is present in any of the inclination angle distributions of 0 to 10 degrees, and the sum of the frequency distributions of the inclination angle distributions of 0 to 10 degrees accounts for 45% or more of the sum of the frequencies of the entire inclination angle distribution. A surface-coated cutting tool comprising:
2. The surface-coated cutting tool according to claim 1, characterized in that the crystal grains are columnar crystals having an area-weighted average crystal grain width of 0.1 to 2.0 μm and an area-weighted average aspect ratio of 2.0 to 10.0, and have a repeated change in the Al content rate within the grains along any one of equivalent crystal orientations represented by <001>, with the Al content rate taking maximum and minimum values, and a difference Δx between the average value of the maximum values and the average value of the minimum values of x being 0.03 to 0.
10.
3. The surface-coated cutting tool according to claim 1 or 2, characterized in that the crystal grains are columnar crystals having an average crystal grain width of 0.1 to 2.0 μm and an average aspect ratio of 2.0 to 10.0, and have a repeating change in which the Al content ratio takes a maximum value and a minimum value within the grain along any one of equivalent crystal orientations represented by <001>, an average interval of the repeating change is 3 to 100 nm, and a change width x0 of x in a plane perpendicular to the orientation is 0.01 or less.
4. The lattice constant a of the crystal grains is the lattice constant a of cubic VN. VN and the lattice constant a of cubic AlN AlN For 0.05a VN +0.95a AlN ≦a≦0.24a VN +0.76a AlN 4. The surface-coated cutting tool according to claim 1, wherein the following relationship is satisfied:
5. 5. The surface-coated cutting tool according to claim 1, wherein the composite nitride or composite carbonitride layer is composed only of crystal grains of the composite nitride or composite carbonitride having a NaCl type face-centered cubic structure.
6. The surface-coated cutting tool according to any one of claims 1 to 4, characterized in that the composite nitride or composite carbonitride layer contains fine crystal grains having a hexagonal crystal structure, the fine crystal grains occupying an area ratio of 30% or less, and the fine crystal grains have an average grain size of 0.01 to 0.30 µm.
7. 7. The surface-coated cutting tool according to any one of claims 1 to 6, characterized in that a lower layer is present between the tool substrate and the V and Al composite nitride layer or composite carbonitride layer, the lower layer being made of one or more Ti compound layers selected from a Ti carbide layer, a nitride layer, a carbonitride layer, a carbonate layer and a carbonitride-oxycarbonate layer, and having a total average layer thickness of 0.1 to 20.0 μm.
8. The surface-coated cutting tool according to any one of claims 1 to 7, characterized in that an upper layer including at least an aluminum oxide layer is present on the upper portion of the composite nitride layer or composite carbonitride layer, with a total average layer thickness of 1.0 to 25.0 μm.
Citation Information
Patent Citations
Coated cutting tool
JP2005271106A
Hard coating, target for forming hard coating, and method for forming hard coating
JP2006249574A
Surface coat cutting tool having hard coat layer exhibiting superior chipping resistance
JP2016064471A
Surface coat cutting tool having hard coat layer exhibiting superior chipping resistance
JP2016064485A
Surface-coated cutting tool excellent in chipping resistance and wear resistance
JP2016137537A